An adaptive spectral index for carbonate rocks using OLI Landsat-8 imagery. Issue 1 (31st December 2023) - Sales, V. F.; Zanotta, D. C.; Marques Jr., A.; Racolte, G.; Muller, M.; Cazarin, C. L.; Ibanez, D.; Gonzaga Jr., L.; Veronez, M. R.
Abstract: The accurate characterization of carbonate rocks is crucial for determining the potential for exploring outcrops in the oil industry. Modern remote sensing instruments have played an important role in estimating mineral characteristics in the most varied scales. However, mathematical expressions suggested for converting radiance values to mineral information are often designed to work in only one particular territory. At the same time, the few general solutions existing tend to achieve overall poor results. In this paper, we propose an adaptive approach to estimate subpixel amounts of carbonate rocks using OLI-Landsat 8 image data. The main formulation is derived from exhaustive analysis of the spectral behavior of several carbonate materials. The formulation is subsequently adapted through the use of a genetic algorithm to work on diverse situations. Experiments have demonstrated the adaptability of the method for different environments, as well as its higher performance when compared with existing carbonate indices.